2012
DOI: 10.1038/jcbfm.2012.21
|View full text |Cite
|
Sign up to set email alerts
|

Neuroglobin Regulates Hypoxic Response of Neuronal Cells through Hif-1α- and Nrf2-mediated Mechanism

Abstract: Oxygen sensing in hypoxic neurons has been classically attributed to cytochrome c oxidase and prolyl-4-hydroxylases and involves stabilization of transcription factors, hypoxia-inducible factor-1a (Hif-1a) and nuclear factor erythroid 2-related factor 2 (Nrf2) that mediate survival responses. On the contrary, release of cytochrome c into the cytosol during hypoxic stress triggers apoptosis in neuronal cells. We, here advocate that the redox state of neuroglobin (Ngb) could regulate both Hif-1a and Nrf2 stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 39 publications
4
38
0
Order By: Relevance
“…The underlying mechanisms responsible for this discrepancy are unclear. We assume that HIF-1α activated by SE stimulates different signaling pathways in the cellular nucleus and cytoplasm that regulate expression of PICs due to different HIF-1α-targeted genes [5,6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The underlying mechanisms responsible for this discrepancy are unclear. We assume that HIF-1α activated by SE stimulates different signaling pathways in the cellular nucleus and cytoplasm that regulate expression of PICs due to different HIF-1α-targeted genes [5,6].…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated subunit HIF-1α in the cellular nucleus and cytoplasm modulates the expression of several target genes which are involved in neuroprotection, erythropoiesis, and apoptosis modulation [5,6]. Additionally, inadequate oxygen supply is likely to appear in the brain regions during SE, which is associated with seizure-evoked behavioral activities [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated subunit HIF-1α in the cellular nucleus and cytoplasm modulates the expression of several target genes that involve in neuroprotection, erythropoiesis, and apoptosis modulation [11,12]. Additionally, inadequate oxygen supply appears in the brain regions during global ischemia, which is associated with ischemiaevoked pathophysiologic changes [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study showed that Ngb regulates Hif1α and Nrf2 (Nfe2l2) expression and antioxidant levels in cells exposed to hypoxia (26). Therefore, the following genes were chosen for differential expression analysis using RT-qPCR in the dark-adapted retina: Hif1α, the Hif1α target gene Bnip3 (27), the glutathione system genes Gsr and Gstz1, the master regulator of oxidative stress responsive genes Nfe2l2 (28) and the unfolded protein response regulator Xbp1 (29).…”
Section: H 5 H ------------------------------------------------------mentioning
confidence: 99%